Structural, electrical and magnetic properties of high concentration in doped La⅔ Ca⅓ MnO3 / Abdullah Chik …[et al.] - Chik, Abdullah; Halim, S. A.; Lim, K.P.; K., Kabashi; Salleh, Saafie (2004)
Structural and electrical properties of high concentration of indium doped AB03 typed colossal magnetoresistance La⅔ Ca⅓ MnO3 (LCMO) perovskite were studied using DC four point probe system, X ray diffractometry, and scanning electron microscopy. (Lal-x Inₓ)⅔Ca⅓ MnO3 (LICMO) samples of concentration x = 0.0, 0.4, 0.5 and 0.6 with sample x=0.0 as a reference were prepared using the solid state reaction method. XRD study shows Indium doped samples exhibit the effect of reduced <rᴀ> ionic radius with the decreasing of the cell volume of the samples with increasing In concnetration. XRD study also shows appearance of secondary phase with increasing intensity with incorporation of indium. SEM micrographs shows porosity decreased with high In doping with fused grains and unclear grain boundaries. Electrical transport studies show the metal to insulator transition temperature Tp is hugely dropped to lower temperature from 194 K of x=0.0 to 70.9 Kat x=0.4 and is slightly decreased with further In doping. Ac susceptibility shows that ferromagnetic interactions are decreasing with increasing In content suggesting weakening DE interactions.